Downregulation of miR-146a-5p Inhibits Choroidal Neovascularization via the NF-κB Signaling Pathway by Targeting OTUD7B. (1st December 2020) - Li, Longhui; Lai, Kunbei; Gong, Yajun; Huang, Chuangxin; Xu, Fabao; Li, Yingqin; Jin, Chenjin
ABSTRACT: Purpose: Choroidal neovascularization (CNV) is the key pathological change caused by irreversible blindness resulting from neovascular AMD (nAMD). However, the pathological mechanisms underlying CNV remain largely unknown. Here, we aimed to investigate the role of miR-146a-5p in CNV formation. Materials and Methods: At the cellular level, we overexpressed or downregulated miR-146a-5p in an umbilical vein endothelial cell line (EA.hy926) by transfecting cells with either a miR-146a-5p mimic or an inhibitor. CCK8, wound healing, and Matrigel assays were performed to examine the proliferation, migration, and tube formation of endothelial cells (EA.hy926). Target relationship between miR-146a-5p and OTUD7B was verified using a double luciferase reporter experiment. An experimental CNV model was established by treating fundi of male C57BL/6 J mice with 810 nm laser. Fundus fluorescein angiography (FFA) was performed to evaluate the leakage of CNV on day 7 after miR-146a-5p antagomir intravitreal injection. The CNV volume was measured using Choroidal Flatmounts in a confocal study. The expression levels of VEGF, ICAM1, and NF-κB (p50 and p65) were detected both in vitro and in vivo. Results: The expression of miR-146a-5p was increased in LPS-stimulated endothelial cells and in experimental CNV RPE-choroidal complexes in mouse models. LPS-induced proliferation, migration, and tube formation were inhibited by the miR-146a-5p inhibitor. The miR-146a-5p antagomir attenuated CNV formation and fluorescent leakage in the vivo CNV model. In the LPS-stimulated endothelial cells and the CNV mouse model, the NF-κB signaling pathway was activated and the expression of VEGF and ICAM1 increased. Conversely, downregulation of miR-146a-5p inactivated the NF-κB signaling pathway and reduced the expression of VEGF and ICAM1. Conclusions: Our results indicated that downregulation of miR-146a-5p inhibited experimental CNV formation via inactivation of the NF-κB signaling pathway.